(untitled) (Ameghiniana, 2013)
Brachyphyllum. tigrense a new Conifer from the Baqueró Forrnation, Cretaceous of Santa Cruz.- A new species, Brachyphyllum tigrense is desrcribed. It has been found in the Bajo Tigre locality, in two different plants beds. In one of these beds, Brachyphyllum tigrense is the almost exclusive elemento Brachyphyllum.tigrense .differs from the other species of the genus descríbed for the same formation maínly on its cuticular structure.